2005
DOI: 10.1097/01.ju.0000146631.14200.d4
|View full text |Cite
|
Sign up to set email alerts
|

High Power (80 W) Potassium-Titanyl-Phosphate Laser Vaporization of the Prostate in 66 High Risk Patients

Abstract: Our initial experience indicates that 80 W KTP laser vaporization is a virtually bloodless and, hence, safe but effective treatment option in seriously ill patients or those on oral anticoagulants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
95
2
19

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 233 publications
(125 citation statements)
references
References 19 publications
(13 reference statements)
9
95
2
19
Order By: Relevance
“…Importantly, as in other studies [10,16], there was no TUR syndrome. However, there was severe macrohaematuria after surgery, with one patient requiring a blood transfusion and cystoscopic clot removal.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Importantly, as in other studies [10,16], there was no TUR syndrome. However, there was severe macrohaematuria after surgery, with one patient requiring a blood transfusion and cystoscopic clot removal.…”
Section: Discussionsupporting
confidence: 60%
“…Recent studies showed reduced blood loss and avoidance of TUR syndrome even in high-risk patients [10][11][12]. Thus, the objective of the present study was to use the Greenlight system for treating of BPH in prostates of ≥ 80 mL, and to investigate the safety and outcome of this procedure, comparing it with results from Greenlight therapy for smaller prostates of < 80 mL.…”
Section: Introductionmentioning
confidence: 99%
“…In studies where patients undergoing TURP or KTP laser prostatectomy were directly compared, the short-term efficacy was equivalent at 6 and 12 months, but with a significantly shorter catheterization and inpatient stays in the laser group [3,4]. It also provides a virtually bloodless operation, and has been used safely and effectively in highrisk candidates on anticoagulation therapy [5,6], with no haemorrhagic complications. There are no reported requirements for blood transfusion.…”
Section: Introductionmentioning
confidence: 99%
“…Qmax values had increased by 250% at 3 months, 242% at 6 months, 255% at 12 months and 278% at 24 months postoperatively. In another study, decreases in IPSS values at 1, 3, 6 and 12 months postoperatively were 42%, 61%, 66% and 68%, respectively, and Qmax values increased by 176%, 182%, 187% and 222%, respectively [12]. Results from Hai [13] established the long-term durability of high-power KTP laser vaporization, demonstrating that it can be used for glands of all sizes, in high-risk and anticoagulated patients, and with minimal morbidity and sustained clinical outcomes.…”
Section: Discussionmentioning
confidence: 87%